What is the cost of pension reform reversal in Slovakia and could the NDC scheme solve the fiscal imbalance of payg scheme? - Šebo, Ján; Danková, Daniela; Králik, Ivan (Lodz University of Technology Press, 2021)
In this study, by applying microsimulation pension model supported by statistical and administrative data on Slovak population, we analyze the fiscal and redistributive consequences of retirement age ceiling and impact of NDC scheme introduction on the Slovak pay-as-you-go pillar fiscal balance and expected pension benefits. However, we work with some limitations on the NDC set-up according to the preferences defined by the governmental institutions. The paper is organized as follows: The second section discusses current knowledge and existing papers dealing with pension reform, reform reversals supported by rising pension populism and existing experience with the introduction of NDC schemes. Third section presents more details on Slovak pension system and elaborates details on the research objective, data, and methodology with the presentation of no-policy change set-up as well as NDC scheme set-up. Fourth section presents the research results of the fiscal and redistribution implications of the policies examined and discusses the findings and potential challenges that need to be further elaborated if the NDC scheme should be implemented, especially the poverty risk for low-income cohorts and minimum retirement income granted to a retiring person regardless the level of paid contributions.
Keywords: Slovak pay-as-you-go pension scheme; notional defined contribution (NDC) scheme; retirement age; pension schemes